2018
DOI: 10.1007/s00431-018-3304-x
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of gastrostomy insertion for children and adolescents with intellectual disability

Abstract: Prof Forbes conceptualized and designed the study, was responsible for obtaining funding, reviewed and revised the manuscript, and critically reviewed the manuscript for important intellectual content regarding aspects of gastroenterology. Dr Ravikumara conceptualized and designed the study, was responsible for obtaining funding, reviewed and revised the manuscript, and critically reviewed the manuscript for important intellectual content regarding aspects of gastroenterology. A/Prof Jacoby conceptualized and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 39 publications
2
26
0
Order By: Relevance
“…Children who were <3 years of age when undergoing gastrostomy in our more recent cohort seemed to experience fewer hospitalizations overall, consistent with models of care characterized by more accessibility to proactive management during the early years. 24,28 There is a causal relationship between gastrostomy insertion and aggravation of gastroesophageal reflux and aspiration pneumonia, but studies have had small sample sizes. 29 An exception was a large Canadian data linkage study of feeding tube placements in 948 children with neurologic impairment, which found no difference in hospitalization for reflux-related issues 2 years after the procedure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Children who were <3 years of age when undergoing gastrostomy in our more recent cohort seemed to experience fewer hospitalizations overall, consistent with models of care characterized by more accessibility to proactive management during the early years. 24,28 There is a causal relationship between gastrostomy insertion and aggravation of gastroesophageal reflux and aspiration pneumonia, but studies have had small sample sizes. 29 An exception was a large Canadian data linkage study of feeding tube placements in 948 children with neurologic impairment, which found no difference in hospitalization for reflux-related issues 2 years after the procedure.…”
Section: Discussionmentioning
confidence: 99%
“…23 , illustrating earlier gastrostomy in more recent years. 24 Fundoplication was carried out in less than one-third of individuals with gastrostomy insertion (cohort 1: n = 91 [28.0%]; cohort 2: n = 138 [30.3%]).…”
Section: Statistical Analysesmentioning
confidence: 99%
“…A study analysing data over time in the whole paediatric population in the USA showed that the number of procedures for gastrostomy increased every year from 1997 to 2009 6. Also studies from Australia and Sweden have shown increase over time in the insertion and use of permanent feeding tubes in the paediatric population 14 15. It is likely that surgeries for gastrostomy also increased in the geographical areas included in our study during the 20-year study period.…”
Section: Discussionmentioning
confidence: 70%
“…These time trends appear to indicate that survival for children with gastrostomy is improving with time, consistent with changing and more proactive clinical care models including greater use of intensive care services (Wong et al . 2019). Nevertheless, compared with matched controls, our findings have shown that the procedure remained associated with lower survival in WA‐born children and adolescents diagnosed with severe ID.…”
Section: Discussionmentioning
confidence: 99%
“…2017; Wong et al . 2019). We categorised gestational age into five groups: very preterm (24–31 weeks), moderate and late preterm (32–36 weeks), early term (37–38 weeks), full term (39–40 weeks) and post‐term (≥41 weeks) based on dating ultrasound and last menstrual period where dating ultrasound was not available (American College of Obstetricians and Gynecologists 2013).…”
Section: Methodsmentioning
confidence: 99%